Anhysteretic remanent magnetization: model of grain size distribution of spherical magnetite grains - Vasquez, Carlos Alberto (2018)
A phenomenological model based on a linear relationship between the magnetic coercivity field and the reciprocal of the grain diameter is applied to explain the anhysteretic remanent magnetization (ARM) imparted to artificial samples with different concentrations of a very well characterized magnetite powder. By analyses of scanning electron microscopy images, the spherically shaped single domain synthetic magnetite is found to follow a lognormal grain size distribution with ~86 nm of mean diameter. The proposed model, fitted to ARM measurements up to a peak alternating field of 100 mT, yields a very good agreement. The coercivity behaviour predicted by micromagnetism theory disagrees with the experimental results of this work. A likely explanation for the discrepancy is that the magnetite particles, which consist of a mixture of grains in coherent rotation and curling modes, produce similar observations as domain processes.